Evaluation of Web-Based Academic Management Information System Products in Improving Academic Administration - Rini Ade Octaviany; Arif Rahman; Yuniarto Mudjisusatyo (Universitas Negeri Makassar, 2024)
The issues that arise regarding the efficiency and effectiveness of academic management, one of which is due to the need for integration of activities using information technology. This research aims to develop a web-based academic information system product using the Research & Development (R&D) method and the ADDIE model. The study involves teachers and students at SMA Negeri 9 Banda Aceh and several experts in the development and implementation phases. The research results indicate that 90.29% of products in the category are deemed highly suitable through expert judgment validation. Meanwhile, the usability results of the product in limited trials were 76; in the main field trial, it was 72; and in the operational field trial, it was 84, categorizing the product as suitable and beneficial for schools in managing academic activities to enhance the effectiveness of school academic management. The implications of this research indicate the potential to improve academic management activities by integrating technology, thereby reducing administrative burdens, saving time, optimizing resource utilization, and assisting stakeholders in decision-making.